Link reversal and reactive routing in Low Power and Lossy Networks - Chi-Anh La; Heusse, Martin; Grenoble, Andrzej Duda (2013 IEEE 24th Annual International Symposium on Personal, Indoor, and Mobile Radio Communications (PIMRC), 2013)
In this paper, we study current routing issues in Low Power and Lossy Networks (LLNs) and propose two enhancements to the RPL routing protocol. First, we focus on the establishment and maintenance of the Destination Oriented Directed Acyclic Graph (DODAG) for upward traffic and propose a low overhead mechanism that guarantees the absence of loops and quickly reacts to topology changes using a link reversal algorithm. Second, we propose either proactive or on demand establishment of downward routes from the DODAG root to leaf nodes. Simulation results show that our enhancements reduce the convergence time, generate less routing messages, and improve the performance in a network subject to link failures.